Evaluating the impact of various seed priming agents on germination behaviour of Bael (Aegle marmelos L.) - Chandramohan Reddy, G; Anusha, Siriki; Banala , Gladis; Rajeshwari, G; Vinod Kumar, N; Ramanjaneya Reddy, A; Sreelatha, P; Hari Mallikarjuna Reddy, B (Plant Science Today, 2025)
The bael seeds has poor germination and higher seedling mortality during nursery stage. Therefore, it becomes important to standardize the pre-seed treatment protocol and exact concentration of hormone and other chemicals for higher seed germination and seedling growth for commercial bael nursery - industry in India. Hence, the present study was planned to determine the effect of the priming agents on seed germination, seedling growth of Bael (Aegle marmelos L. Correa). Effect of seed priming agents like H2O, GA3, H2O2, NAA at different concentrations on seed germination and growth of bale seedling grown under shade net house was observed in the present study. All the seedling characters were measured as per ISTA guidelines. Among the priming agents GA3 200 ppm recorded as the best priming treatment with respect to the parameters, viz. germination percentage (89.92 %), shoot length (20.53), number of leaves per plant (2.11), root diameter (3.50 cm), root length (23.22 cm), fresh weight of plant (6.21 g), dry weight of plant (3.48 g), Vigour index I (1845), Vigour index II (2088) and Vigour index III (313) than other seed priming treatments. The results highlight how priming can significantly improve the germination and growth of bael seedlings; the GA3 at 200 ppm solution treatments stand out as particularly successful technique for the better germination and establishment of Bael nursery under shade net house conditions.